Transmetacarpal replantation: a case report - Erić, Dražan; Kovačević, Maksim; Dostić, Milivoje; Djordjević-Marić, Sanja; Kojić, Siniša; Kapor, Slobodan; Ninković, Milomir (Vojnosanitetski pregled, 2024)
Introduction. Transmetacarpal amputation (TA) distal to the superficial palmar arch is one of the most difficult procedures in replantation surgery because it requires the reconstruction of blood vessels, muscles, tendons, bones, nerves, and skin. We present a case of a patient with TA of the left hand and microsurgical replantation. Case report. A 23-year-old left-hand dominant male worker with a positive smoking history sustained TA from a radial saw blade and avulsion injury of the palmar side of the thumb with no other apparent injuries. The time between the amputation and replantation was 4 hrs. The patient sustained the amputation at the level of metacarpophalangeal joints. The successful replantation included: wound and intrinsic muscles debridement, microvascular anastomoses of the blood vessels, internal fixation of the metacarpal bones, neurorrhaphy, tenorrhaphy, and wound closure with local skin flap for thumb soft tissue defect. The patient was followed for seven years postoperatively. Conclusion. The replantation surgery requires a specialized department and well-educated teams of hand microsurgeons, orthopedic surgeons, and anesthesiologists. The most important factors that influenced the outcome after the replantation in the presented case included the type and level of injury, ischemia time, comorbidities, age, smoking history, and physical therapy.